2020
DOI: 10.1007/s12208-020-00256-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patterns of alumni commitment in key strategic relationship programmes

Abstract: Higher education institutions (HEIs) need to understand their alumni when drawing strategic relationship programmes. This paper aims to identify clusters of alumni based on their commitment relationship and to analyse factors influencing their intention to collaborate with the HEI. The study took place at a Portuguese university, considering a dataset of 1075 of alumni asserting intention to collaborate. First, a cluster analysis was conducted to identify patterns of commitment relationship. Secondly, a logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
1
4
0
5
Order By: Relevance
“…They should focus on different segments of their student/alumni population (e.g., enrolled students versus alumni, first-year experience versus students' experiences from higher years). In line with recent findings (Pedro et al, 2020a(Pedro et al, , 2020b, as we indicated in Study 4 (Chapter 5), it would be interesting for higher education institutions to examine whether alumni still want to be involved with their alma mater; if so, in what way.…”
Section: Student Loyaltysupporting
confidence: 70%
See 4 more Smart Citations
“…They should focus on different segments of their student/alumni population (e.g., enrolled students versus alumni, first-year experience versus students' experiences from higher years). In line with recent findings (Pedro et al, 2020a(Pedro et al, , 2020b, as we indicated in Study 4 (Chapter 5), it would be interesting for higher education institutions to examine whether alumni still want to be involved with their alma mater; if so, in what way.…”
Section: Student Loyaltysupporting
confidence: 70%
“…To improve the formation of bonds with students, higher education policymakers and educational practitioners should strategically focus on relational aspects of their students' educational service experience. As proposed, alumni should be actively involved in establishing an alumni culture where long-term relationships exist, in order to sustain those relationships (Pedro et al, 2020a(Pedro et al, , 2020bSchlesinger et al, 2017). In such a way, students, alumni, and higher education institutions could benefit from the educational experience they all create together.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations